Improving Research on Mathematics Learning and Teaching in Rural Contexts - William S. Bush (Journal of Research in Rural Education, 2005)
An adequate research base for mathematics learning and teaching in rural areas does not exist. According to Silver (2001), mathematics education research has virtually ignored rural context, even though approximately one third of the nation's population lives in rural areas. Mathematics education and rural education researchers seem to have little understanding of each other's work. In response to this disconnect, I describe ethnomathematics in mathematics education and placebased pedagogy in rural education and, in turn, discuss how research in place-based pedagogy can benefit from research methodologies in ethnomathematics. Specifically, I offer (a) an overview and analysis of current issues regarding mathematics in rural contexts; (b) a broader view of the role of mathematics in rural contexts and in place-based pedagogy; and (c) recommendations for much needed collaboration in research and practice in mathematics education in rural contexts.